Determinants of day-night difference in blood pressure in subjects of African ancestry - Maseko, Joseph Muzi (My University, 2009)
Hypertension is a major risk factor for cardiovascular disease in both developed and developing countries. Blood pressure normally decreases at night and a number of studies have indicated that a reduced nocturnal decline in blood pressure (BP) increases the risk for cardiovascular disease. Nocturnal decreases in BP are attenuated in subjects of African as compared to European descent, but the mechanisms of this effect require clarity. In the present study I attempted to identify potentially modifiable factors that contribute toward nocturnal decreases in BP in a random sample of 171 nuclear families comprising 438 black South Africans living in Soweto. Prior studies have suggested that adiposity and salt intake may determine nocturnal decreases in BP. Adiposity and salt intake were considered to be potentially important factors to consider in the present study as 67% of the group studied were either overweight or obese and in 291 subjects that had complete 24-hour urine collections (used to assess salt intake) and BP measurements, Na+ and K+ intake was noted to be considerably higher and lower respectively than the recommended daily allowance in the majority of people. Moreover, a lack of relationship between either hypertension awareness and treatment and Na+ and K+ intake suggested that current recommendations for a reduced Na+ intake and increased K+ intake in hypertensives do not translate into clinical practice in this community. In order to assess whether adiposity or salt intake are associated with nocturnal decreases in BP in this community, ambulatory BP monitoring was performed using Spacelabs model 90207 oscillometric monitors. Of the 438 subjects recruited, 314 had ambulatory BP measurements that met pre-specified quality criteria (more than 20 hours of recordings and more than 10 and 5 readings for the computation of daytime and nighttime means respectively). To identify whether adiposity or salt intake are associated with a reduced nocturnal decline in BP, non-linear regression analysis was employed with indices of adiposity and urinary Na+ and K+ excretion rates and urine Na+: K+ ratios included in the regression model with adjustments for potential confounders. Neither body mass index, skin-fold thickness, waist circumference, waist-to hip ratio, urinary Na+ and K+ excretion rates, nor urine Na+: K+ ratios were associated with nocturnal decreases in systolic and diastolic BP. Indices of adiposity were however associated with 24 hour ambulatory systolic and diastolic BP. Unexpectedly, female gender was associated with an attenuated nocturnal decrease in BP. In conclusion, in the first random, community-based sample with large sample sizes conducted with ambulatory BP monitoring in Africa, I found that neither adiposity nor salt intake are associated with a reduced nocturnal decline in BP. The lack of association between either salt intake or adiposity and nocturnal decreases in BP was despite a high prevalence of excessive adiposity in the community, as well as clear evidence that current recommendations for a reduced Na+ intake and increased K+ intake do not translate into clinical practice in this community. Thus, based on this study, the question arises as to whether primordial prevention programs targeting excess adiposity or inappropriate salt intake are likely to modify nocturnal decreases in BP, in urban, developing communities of African ancestry in South Africa. However, unexpectedly I noted that females were more likely to have an attenuated nocturnal decrease in BP. Thus further work is required to explain this finding.
Keywords: blood pressure; Africans; day-night difference